Hierarchical Design of Connected Cruise Control in the Presence of Information Delays and Uncertain Vehicle Dynamics - Linjun Zhang; Jing Sun; Orosz, Gabor (IEEE transactions on control systems technology, 2018)
In this paper, we investigate the design of connected cruise control that exploits wireless vehicle-to-vehicle communication to enhance vehicle mobility and safety. A hierarchical framework is used to reduce the complexity for design and analysis. A high-level controller incorporates the motion data received from multiple vehicles ahead and also considers information delays, in order to generate the desired longitudinal dynamics. At the lower level, we consider a physics-based vehicle model and design an adaptive sliding-mode controller that regulates the engine torque, so that the vehicle can track the desired dynamics in the presence of uncertainties and external perturbations. Numerical simulations are used to validate the analytical results and demonstrate the robustness of the controller.